Folk crafts are the result of the labor of the Uzbek people, the product of their conscious activity aimed at understanding artistry, harmony and beauty. - Magdieva Marxabo Erkinovna (Miasto Przyszłości, 2023)
One of the most important tasks of today is to educate well-rounded, goal-oriented and energetic young people who have modern knowledge and skills and who can take responsibility for the country’s worthy future. through giving them insights about our national values and customs, traditions, and pedagogical possibilities and prerequisites for career orientation